2008
DOI: 10.1016/j.molcel.2008.07.006
|View full text |Cite
|
Sign up to set email alerts
|

RecQ Helicase, Sgs1, and XPF Family Endonuclease, Mus81-Mms4, Resolve Aberrant Joint Molecules during Meiotic Recombination

Abstract: Summary Saccharomyces cerevisiae RecQ helicase, Sgs1, and XPF-family endonuclease, Mus81-Mms4, are implicated in processing joint molecule (JM) recombination intermediates. We show that cells lacking either enzyme frequently experience chromosome segregation problems during meiosis and when both enzymes are absent attempted segregation fails catastrophically. In all cases, segregation appears to be impeded by unresolved JMs. Analysis of the DNA events of recombination indicates that Sgs1 limits aberrant JM str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
216
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(230 citation statements)
references
References 55 publications
13
216
1
Order By: Relevance
“…Possibly, the comparatively higher frequency of MLH1-negative RNs in heterochromatin is related to the high frequency of repetitive sequences (32). Such sequences may be more likely to form unusual and complex recombination intermediates that can be resolved as COs by the MUS81-dependent CO pathway (6,29,34,35). At a more applied level, modifying local recombination frequencies in pericentric regions is an important challenge for plant breeding (e.g., for positional cloning), and knowing that heterochromatic regions are more prone to class II COs may lead to new strategies to promote COs in those regions, e.g., by mutating the FANCM gene that has been shown to specifically suppress class II COs in Arabidopsis (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, the comparatively higher frequency of MLH1-negative RNs in heterochromatin is related to the high frequency of repetitive sequences (32). Such sequences may be more likely to form unusual and complex recombination intermediates that can be resolved as COs by the MUS81-dependent CO pathway (6,29,34,35). At a more applied level, modifying local recombination frequencies in pericentric regions is an important challenge for plant breeding (e.g., for positional cloning), and knowing that heterochromatic regions are more prone to class II COs may lead to new strategies to promote COs in those regions, e.g., by mutating the FANCM gene that has been shown to specifically suppress class II COs in Arabidopsis (14).…”
Section: Resultsmentioning
confidence: 99%
“…Interference from early class I COs would lead to a higher proportion of class II COs occurring away from the initiation regions (see below for evidence of interaction between the two pathways). Furthermore, any recombination intermediates that form among the repetitive sequences in pericentric heterochromatin may be more likely to have aberrant structures that require MUS81 for resolution (34), leading to a comparatively high frequency of MLH1-negative RNs in heterochromatin.…”
Section: Resultsmentioning
confidence: 99%
“…These two phenotypes are similar to the meiotic depletion alleles of top3/rmi1 that disrupt decatenase activity and lead to the accumulation of unresolved JMs. These mutations block nuclear divisions without disrupting the meiotic program, also known as "meiotic catastrophe" (Gangloff et al 1999;Jessop and Lichten 2008;Oh et al 2008;Kaur et al 2015;Tang et al 2015). Similar to the top3/rmi1 mutants, deletion of SPO11 or mutating the catalytic residue of SPO11 (SPO11-Y135F) suppressed the nup2D ndj1D block to nuclear divisions, presumably by eliminating a physical constraint caused by intermediates, or aberrant structures, associated with meiotic recombination.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast mitotic cells, we and others demonstrated that two DNA helicases, Sgs1 and Srs2, suppress crossovers in DSBinduced and spontaneous recombination, but in different ways (Ira et al 2003;Lo et al 2006;Robert et al 2006). Sgs1 was also shown to suppress crossing over in the meiotic cycle, particularly when three or four chromatids are involved in recombination (Jessop et al 2006;Oh et al 2007Oh et al , 2008Jessop and Lichten 2008). Srs2 appears to promote steps in the SDSA pathway, whereas Sgs1 and its associated topoisomerase Top3 reduce crossovers apparently by resolving the dHJ in a noncrossover manner.…”
mentioning
confidence: 91%